BUDAYA ANDHAP ASOR MASYARAKAT MADURA DALAM KOMUNIKASI KONSELING - Ach. Maulidi; Firosal Jamilah; Hesty Nerizza; Lum’atul Helmiyah; Nazlah Maghfiroh Agustin; Putri Damayanti; Rusmiyati (Universitas Muhammadiyah Metro, 2026)
This study aims to examine the implementation of the Andhap Asor culture in counseling communication using a qualitative approach with a literature review method. The value of Andhap Asor in Madurese culture describes a person as having humble behavior, politeness, and respect for one another. Andhap Asor culture is one of the important values ​​that can influence the dynamics of communication in the counseling process, especially in building a therapeutic relationship between the counselor and counselee. The research method used is a literature review by examining several research sources found in Google Scholar and published between 2021-2026. The keywords used to explore the information are